Factor and Demand Conditions Shaping Production Effectiveness in Remote MSMEs: A Case Study of Luci Snack in North Kalimantan - Alhadi, Saadiq; Asyari, Hasyim (Jurnal Vokasi Indonesia, 2026)
The production effectiveness of agro-industrial MSMEs in remote frontier regions is severely hampered by geographic isolation and lack of basic infrastructure. This study examines the unique case of Luci Snack in North Kalimantan, operating without state electricity or land access. The research aims to analyze how the interaction between Factor Conditions (river logistics and technology) and Demand Conditions influences Production Effectiveness. Employing an embedded single-case study design, data were collected via in-depth interviews with the owner and village officials, participant observation, and documentation, then analyzed using the Miles, Huberman, and Saldaña (2014) interactive model. Findings reveal a paradox: (1) Production effectiveness is not interpreted conventionally as speed or volume, but redefined as an absolute commitment to quality consistency; (2) Limitations in manual technology and isolated logistics are capitalized upon as a "traditional" Unique Selling Point; (3) This superior quality generates a loyal demand pattern that tolerates production speed inefficiencies. The implication is that sustainability for remote MSMEs depends on transforming infrastructure limitations into premium product differentiation rather than volume-based competition.